Análise das emissões gasosas de um veículo flex funcionando com diferentes combustíveis - Holanda, Raphael Araujo de (2011)
Efforts in research and development of new technologies to reduce emission levels of pollutant gases in the atmosphere has intensified in the last decades. In this context, it can be highlighted the modern systems of electronic engine management, new automotive catalysts and the use of renewable fuels which contributes to reduce the environmental impact. The purpose of this study was a comparative analysis of gas emissions from a automotive vehicle, operating with different fuels: natural gas, AEHC or gasoline. To execute the experimental tests, a flex vehicle was installed on a chassis dynamometer equipped with a gas analyzer and other complementary accessories according to the standard guidelines of emission and security procedures. Tests were performed according to NBR 6601 and NBR 7024, which define the urban and road driving cycle, respectively. Besides the analysis of exhaust gases in the discharge tube, before and after the catalyst, using the suction probe of the gas analyzer to simulate the vehicle in urban and road traffic, were performed tests of fuel characterization. Final results were conclusive in indicating leaded gasoline as the fuel which most contributed with pollutant emissions in atmosphere and the usual gasoline being the fuel which less contributed with pollutant emissions in atmosphere